f(m) = 2m + 2 (explicit expression)
f(n) = 2n - 3 (explicit expression)
f() = -n + 5 (explicit expression)
f(n) = f(n-1) - 1 (recursive expression)
{4, 3, 2, 1, ... } where f(1) = 4 and f(n) = f(n-1) - 1 for n >= 1 (sequence)
{-1, -2, -3, -4, ... } where f(1) = -1 and f(n) = f(n-1) - 1 for n >= 1 (sequence)
{-1, 1, 3, 5, ... } where f(1) = -1 and f(n) = f(n-1) + 2 for n >= 1 (sequence)
Match the sequence and recursive expression to its explicit expression. (2 points)
f(m) ニール
f (n) = 2n-3
f() =-n+5
f (n) = 2m+2
= {4, 3, 2, 1, ... } where f (1) = 4 and f (n) = f (n - 1) - 1 forn S 1
# 14, 6, 8, 10,....] where f.(1) = 1 and J (n) = / (n - 1) + 2 for n. >
= {-1, - 2, - 3, - 4,... } where / (1) = -1 and f (n) = f(n - 1) - 1 forn > 1
# {-1, 1, 3, 5,.. . } where f(1) = - 1 and f(n) = f(n - 1) + 2 form > 1
1 answer